Ethnobiological Classification : Principles of Categorization of Plants and Animals in Traditional Societies. - Berlin, Brent (Princeton University Press, 2014)
A founder of and leading thinker in the field of modern ethnobiology looks at the widespread regularities in the classification and naming of plants and animals among peoples of traditional, nonliterate societies--regularities that persist across local environments, cultures, societies, and languages. Brent Berlin maintains that these patterns can best be explained by the similarity of human beings' largely unconscious appreciation of the natural affinities among groupings of plants and animals: people recognize and name a grouping of organisms quite independently of its actual or potential.
Cover.
Keywords: Folk classification -- Cross-cultural studies.; Ethnozoology.; Ethnobotany.; Ethnobotany; Classification anthropologique -- Études transculturelles.; Ethnozoologie.; Ethnobotanique.; SOCIAL SCIENCE -- Anthropology -- General.; SCIENCE -- Life Sciences -- Biology.; Ethnozoology; Folk classification; Cross-cultural studies